Drug resistance in malaria, tuberculosis, and HIV in South East Asia: biology, programme, and policy considerations. (5th September 2017) - Panda, Samiran; Swaminathan, Soumya; Hyder, Khurshid A; Christophel, Eva-Maria; Pendse, Razia N; Sreenivas, Achuthan N; Laksono, Setiwan J; Srivastava, Rahul; Nair, Gopinath B; Aditama, Tjandra Y; Singhasivanon, Pratap; Thapa, Arun B; et al.
Abstract : Malaria, tuberculosis, and HIV present unique challenges in the control of antimicrobial resistance, and require targeted policies, say Samiran Panda and colleagues